Membrane Dialysis for Partial Dealcoholization of White Wines - José Ignacio Calvo; Jaime Asensio; Daniel Sainz; Rubén Zapatero; Daniel Carracedo; Encarnación Fernández-Fernández; Pedro Prádanos; Laura Palacio; Antonio Hernández (Membranes, 2022)
Membrane dialysis is studied as a promising technique for partial dealcoholization of white wines. The performance of three membrane processes applied for the partial dealcoholization of white wines of the Verdejo variety has been studied in the present work. Combination of Nanofiltration with Pervaporation, single step Pervaporation and, finally, Dialysis, have been applied to white wines from same variety and different vintages. The resulting wines have been chemically and sensorially analyzed and results have been compared with initial characteristics of the wines. From the results obtained, we can conclude that all procedures lead to significant alcohol content reduction (2%, 0.9% and 1.23% v/v respectively). Nevertheless, the best procedure consists in the application of Dialysis to the wines which resulted in a reasonable alcohol content reduction while maintaining organoleptic properties (only 14 consumers were able to distinguish the filtered and original wines, with 17 consumers needed to be this differences significant) and consumer acceptability of the original wine. Therefore, membrane dialysis, as a method of partial dealcoholization of white wines, has undoubted advantages over other techniques based on membranes, which must be confirmed in subsequent studies under more industrial conditions. This work represents the first application of Dialysis for the reduction of alcohol content in wines.